Economic Justification of Enterprise Development based on Company Value Analysis - Shcherbakova Natalia A. (SHS Web of Conferences, 2020)
The article considers the use of company value analysis for economic justification of the choice of directions for business development. The company value analysis is based on income forecasting. The authors outline the features of income modelling for these purposes. They consider various ways of forecasting the income of an enterprise for the purpose of economic justification of development options based on annual and quarterly values. The article suggests that the current pandemic situation in the world has significantly affected the performance and development prospects of almost every company making it harder to forecast the performance based on retrospective data due to dramatic changes in income caused by the socio-economic environment in the world. The authors arrived at the conclusion that each specific scenario requires the use of a number of forecast options and selection of the most appropriate forecasting model with regard to every particular situation. In conclusion, it was pointed out that the value analysis of the company gives evident results and can be considered as an effective tool for economic justification of the choice of directions for business development.